2022
DOI: 10.1136/bjsports-2021-104548
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measures in the management of gluteal tendinopathy: a systematic review of their measurement properties

Abstract: ObjectiveEvaluate properties of outcome measures for gluteal tendinopathy.DesignMultistage scoping/systematic review.Data sourcesCochrane, PubMed, Embase, Scopus, Web of Science, PEDro, CINAHL, SPORTDISCUS were searched (December 2021) to identify measures used to evaluate gluteal tendinopathy. Measures were mapped to the core health domains for tendinopathy. Medline, CINAHL, Embase and PubMed were searched (December 2021) for studies evaluating measurement properties of gluteal tendinopathy outcome measures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…A systematic review was undertaken to evaluate the clinimetric properties of the outcome measurements 14. This identified two outcome measurements (the VISA-G (all translations)) and Hip Outcome Score-Brazil that have been studied for clinimetric properties in people with GT.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review was undertaken to evaluate the clinimetric properties of the outcome measurements 14. This identified two outcome measurements (the VISA-G (all translations)) and Hip Outcome Score-Brazil that have been studied for clinimetric properties in people with GT.…”
Section: Resultsmentioning
confidence: 99%
“…HPs, and patients with GT participated in the study. Six stages were undertaken: (1) a scoping review to identify relevant outcome measures (reported separately with stage 3), (2) an online survey of the HPs’ views on the Truth and Feasibility of the outcome measures in line with the Outcome Measures in Rheumatology (OMERACT) guidelines,13 (3) an assessment of the clinimetric properties of identified outcome measures (reported separately14), (4) a second online survey of the HPs which included the results of the former two stages and sought their opinion as to which measurements should be included in the COS, (5) a patient focus group to provide patient insight and (6) an online HP consensus meeting that considered the views of patients and HPs (figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations